Acute exacerbations of interstitial lung disease: what is the best treatment? - Meyer, Keith C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
There is an increasing recognition that patients with various forms of chronic fibrosing interstitial lung diseases (CFILD) are at risk for an acute exacerbation (AE) of their disease that can rapidly lead to death (1). While acute exacerbations of Idiopathic pulmonary fibrosis (AE-IPF) appear to be more common than acute exacerbations for other forms of CFILD and a considerable number of manuscripts have been published on risk factors, pathogenesis and treatments, no randomized and adequately powered clinical trials of therapies for AE-CFILD have been published to date. But because only a relatively small number of patients at any single center develop an AE over time, such a study would be very difficult to perform. Furthermore, funding entities with adequate resources to support a large clinical trial of licensed drugs are reluctant to support an evaluation drugs that are off patent. [...]